Successful Treatment of Severe Pneumonia Caused by Burkholderia cenocepacia With Intravenous Antibiotics and Immunosuppression Under Extracorporal Membrane Oxygenation. Issue 1 (January 2015) - Kirschbaum, Andreas; Seyfer, Perla; Hug, Martin J.; Trittler, Rainer; Pehl, Annika; Koczulla, Andreas-Rembert; Holland, Angelique; Vogelmeier, Claus; Wulf, Hinnerk; Vassiliou, Timon; Rolfes, Caroline
<x xml:space="preserve">Abstract</x> Abstract Purulent destruction–complicated pneumonia is a rare and serious disease of multifactorial genesis. In many cases, the diagnosis cannot be established by microbiological analysis of bronchial aspirates or transbronchial biopsies. In our present case, isolation of the pathogen was only possible by collecting specimens via open surgical lung biopsy. A 57-year-old otherwise healthy man was transferred to our department from another hospital. He presented with progressive respiratory failure while computed tomographic scan showed severe bilateral necrotising pneumonia. With open surgical lung biopsy, we could prove evidence of Burkholderia cenocepacia as causative pathogen. As the patient's pulmonary condition deteriorated and he developed septic multiorgan failure, we initiated extracorporeal membrane oxygenation (ECMO) and commenced aggressive treatment with 4 intravenous antibiotics, cyclosporine, and corticosteroids. With this therapy, the patient's situation rapidly improved; and he was successfully weaned from ECMO and mechanical ventilation. Pneumonia caused by B cenocepacia without underlying pulmonary disease such as cystic fibrosis is an absolute rarity. According to the severity of cepacia syndrome, an interdisciplinary approach including ECMO aggressive antibiotic treatment and immunosuppression was decisive for a successful therapy.